More than 80% of total knee replacements can last for 25 years. (31st December 2019) - Cook, Rob; Davidson, Peter; Martin, Rosie
The study: Evans JT, Walker R, Evans W, Blom AW, Sayers A, Whitehouse MR How long does a knee replacement last? A systematic review and meta-analysis of case series and national registry reports with more than 15 years of follow-up. Published on 16 February 2019 Lancet 2019;393:655-63 This study was supported by the NIHR Biomedical Research Centre at the University Hospitals Bristol NHS Foundation Trust and the University of Bristol. To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000776/more-than-80-of-total-knee-replacements-can-last-for-25-years